Co-contraction in RA patients with a mobile bearing total knee prosthesis during a step-up task - Garling, Eric H.; Wolterbeek, Nienke; Velzeboer, Sanne; Nelissen, Rob G. H. H.; Valstar, Edward R.; Doorenbosch, Caroline A. M.; Harlaar, Jaap (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2008)
It was hypothesized that rheumatoid arthritis (RA) patients with a total knee prosthesis that allows axial rotation of the bearing (MB) will show more co-contraction to stabilize the knee joint during a step-up task than RA patients with a fixed bearing total knee prosthesis (FB) where this rotational freedom is absent while having the same articular geometry. Surface EMG, kinematics and kinetics about the knee were recorded during a step-up task of a MB group ( n = 5), a FB group ( n = 4) and a control group ( n = 8). Surface EMG levels of thigh muscles were calibrated to either knee flexion or extension moments by means of isokinetic contractions on a dynamometer. During the step-up task co-contraction indices were determined from an EMG-force model. Controls showed a higher active ROM during the step-up task than the patient group, 96° versus 88° ( P = 0.007). In the control group higher average muscle extension, flexion and net moments during single limb support phase were observed than in the patient group. During the 20–60% interval of the single limb support, MB patients showed a significant higher level of flexor activity, resulting in a lower net joint moment, however co-contraction levels were not different. Compared to the control group arthroplasty patients showed a 40% higher level of co-contraction during this interval ( P = 0.009). Control subjects used higher extension moments, resulting in a higher net joint moment. Visual analysis revealed a timing difference between the MB and FB group. The FB group seems to co-contract approximately 20% later compared to the MB group. RA patients after total knee arthroplasty show a lower net knee joint moment and a higher co-contraction than controls indicating avoidance of net joint load and an active stabilization of the knee joint. MB and FB patients showed no difference in co-contraction levels, although timing in FB is closer to controls than MB subjects. Since visual analysis revealed a timing difference between the MB and FB group, this may express compensation by coordination. Rehabilitation programs for RA patients should include besides muscle strength training, elements of muscle-coordination training.